Pengaruh Konflik Kerja, Dan Beban Kerja Terhadap Kinerja Karyawan PT. PLN (Persero) UP3 Kota Metro - Lelawati, Nina; Septiani, Ana; Kurniawan, Irvan (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to analyze the effect of work conflict, workload on employee performance.This type of research is a quantitative study with a population of 63 employees registered atPT. Pln (Persero) Up3 Metro City, only 54 samples used were in accordance withpredetermined criteria. The data used is secondary data distribution of questionnaires in theform of a list of questions with several alternative answers for respondents. The statisticaltest used to test the hypothesis was multiple linear regression analysis and was tested usingthe statistical packages for the social science (SPSS) version 26 program. Based on theresults of statistical tests indicate that Work Conflict, Workload has a positive and significanteffect on employee performance.